A Rare Case of an Immunocompetent Male With Zoster Meningitis - Mohammed Ali Faluk MD; Shraddhadevi Makadia MD; Ramy Abdelmaseih MD; S. Mustajab Hasan MD; Khalid Abusaada MD (SAGE Publishing, 2020)
Varicella zoster meningitis is an uncommon complication of herpes zoster, especially in immunocompetent patients. We report a case of a healthy 45-year-old male who developed aseptic meningitis as a result of reactivated varicella zoster virus infection. This case highlights the importance of remaining cognizant of varicella zoster virus as a cause of meningitis in not only the elderly or immunocompromised patients but also in patients who are healthy.